Human Gingiva‐Derived Mesenchymal Stem Cells Elicit Polarization of M2 Macrophages and Enhance Cutaneous Wound Healing - Zhang, Qun‐Zhou; Su, Wen‐Ru; Shi, Shi‐Hong; Wilder‐Smith, Petra; Xiang, Andy Peng; Wong, Alex; Nguyen, Andrew L.; Kwon, Chan Wook; Le, Anh D. (Stem cells (Dayton, Ohio), 2010)
Increasing evidence has supported the important role of mesenchymal stem cells (MSCs) in wound healing, however, the underlying mechanism remains unclear. Recently, we have isolated a unique population of MSCs from human gingiva (GMSCs) with similar stem cell‐like properties, immunosuppressive, and anti‐inflammatory functions as human bone marrow‐derived MSCs (BMSCs). We describe here the interplay between GMSCs and macrophages and the potential relevance in skin wound healing. When cocultured with GMSCs, macrophages acquired an anti‐inflammatory M2 phenotype characterized by an increased expression of mannose receptor (MR; CD206) and secretory cytokines interleukin (IL)‐10 and IL‐6, a suppressed production of tumor necrosis factor (TNF)‐α, and decreased ability to induce Th‐17 cell expansion. In vivo, we demonstrated that systemically infused GMSCs could home to the wound site in a tight spatial interaction with host macrophages, promoted them toward M2 polarization, and significantly enhanced wound repair. Mechanistically, GMSC treatment mitigated local inflammation mediated by a suppressed infiltration of inflammatory cells and production of IL‐6 and TNF‐α, and an increased expression of IL‐10. The GMSC‐induced suppression of TNF‐α secretion by macrophages appears to correlate with impaired activation of NFκB p50. These findings provide first evidence that GMSCs are capable to elicit M2 polarization of macrophages, which might contribute to a marked acceleration of wound healing. STEM CELLS 2010;28:1856–1868